2013
DOI: 10.1371/journal.pone.0084279
|View full text |Cite
|
Sign up to set email alerts
|

BOLD Granger Causality Reflects Vascular Anatomy

Abstract: A number of studies have tried to exploit subtle phase differences in BOLD time series to resolve the order of sequential activation of brain regions, or more generally the ability of signal in one region to predict subsequent signal in another region. More recently, such lag-based measures have been applied to investigate directed functional connectivity, although this application has been controversial. We attempted to use large publicly available datasets (FCON 1000, ADHD 200, Human Connectome Project) to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 61 publications
4
39
0
1
Order By: Relevance
“…We observe opposite patterns of HRF shapes between the thalamus and occipital cortex under the two conditions, which is consistent with the correlation and anti-correlation between the alpha power spectrum and BOLD signal in thalamic and occipital cortex. It is worth to note how the variations in HRF are consistent with the differences in net arterial and venous flow, and the consequent effects on the estimation of Granger causality reported in (Webb, Ferguson et al 2013). This evidence confirms the importance of performing HRF deconvolution prior to estimating not only for lag-based directed connectivity (Wu, Liao et al 2013), but also for standard functional connectivity .…”
Section: Relation With Eeg Powersupporting
confidence: 77%
“…We observe opposite patterns of HRF shapes between the thalamus and occipital cortex under the two conditions, which is consistent with the correlation and anti-correlation between the alpha power spectrum and BOLD signal in thalamic and occipital cortex. It is worth to note how the variations in HRF are consistent with the differences in net arterial and venous flow, and the consequent effects on the estimation of Granger causality reported in (Webb, Ferguson et al 2013). This evidence confirms the importance of performing HRF deconvolution prior to estimating not only for lag-based directed connectivity (Wu, Liao et al 2013), but also for standard functional connectivity .…”
Section: Relation With Eeg Powersupporting
confidence: 77%
“…Figure 2 reports the typical HRF parameters (Height, Time to Peak and Full Width at Half Maximum) for a pool of 32 healthy subjects, as described in [2]. It is worth to note how the variations in HRF are consistent with the differences in net arterial and venous flow, and the consequent effects on the estimation of Granger causality reported in [6]. This confirms the importance of performing HRF deconvolution prior to estimating lag-based directed connectivity.…”
Section: Methodssupporting
confidence: 57%
“…However, as yet, little is known about the directionality of these interactions in large-scale functional networks during the resting state. Estimating directionality from fMRI is challenging due to its limited temporal resolution and indirect relation to neuronal activity (15,16). In contrast, EEG studies in healthy controls have revealed a front-to-back pattern of directed connectivity, particularly in the alpha band (17)(18)(19)(20)(21)(22), consistent with modeling studies that have shown that such patterns may arise due to differences in the number of anatomical connections (the degree) of anterior and posterior regions (22,23).…”
mentioning
confidence: 65%
“…From these time series, the first 20 artifact-free epochs, containing 4,096 samples (3.2768 s), were selected to obtain stable results (70). These time series were then filtered in classical EEG/MEG frequency bands [delta (0.5-4 Hz), theta (4-8 Hz), alpha1 (8-10 Hz), alpha2 (10-13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and lower gamma (30-48 Hz)], using an offline discrete fast Fourier transform filter that does not distort the phases (BrainWave, version 0.9.150.6; home.kpn.nl/stam7883/brainwave.html). Subsequently, the instantaneous phase for each time series was computed by taking the argument of the analytic signal as computed using the Hilbert transform (see e.g., ref.…”
Section: Methodsmentioning
confidence: 99%